الضبطية القضائية المتخصصة في جرائم التغير المناخي: دراسة مقارنة - عطا الله، إمام حسنين خليل (جامعة المنصورة - كلية الحقوق, 2023)
تتجلي المشكلة البحثية لهذه الدراسة في الوقوف على مدي صلاحيات الضبطية القضائية المتخصصة في جرائم التغيرات المناخية وما إذا كانت تتمتع بذات الصلاحيات المقررة للضبطية القضائية العامة في تشريعات الإجراءات الجزائية، أم أن صلاحيتها تقف عند حد تحرير المحاضر؟ وإذا كان الأمر كذلك فهل يتحقق بذلك الجدوى من هذه الضبطية والهدف من إنشاءها والتوسع فيها الملحوظ وخاصة في الجرائم ذات الطبيعة الفنية المعقدة مثل جرائم التغير المناخي، الأمر الذي يستلزم دراسة وتحليل موقف التشريعات الجنائية البيئية من الضبطية القضائية اللازمة لضبط وتعقب مرتكبي الجرائم البيئية وخاصة جرائم التغير المناخي، والصلاحيات والالتزامات والواجبات الممنوحة لهم في كل من مصر والإمارات، وما إذا كانت كافية لملاحقة مثل هذه النوعية من الجرائم المستحدثة. وانتهت الدراسة إلى عدة توصيات أهمها: ١- ضرورة وضع تنظيم تشريعي خاص ومتكامل لمأموري الضبط القضائي المتخصص بصفة عامة ومأموري الضبط في مجال جرائم البيئة والتغيرات المناخية بشكل خاص. ٢ - أن يتضمن هذا التنظيم التشريعي تحديدا واضحا لصلاحيات وسلطات مأموري الضبط القضائي المتخصص في جرائم البيئة والتغيرات المناخية. 3- أن يكون هذا التنظيم التشريعي عام، وبالنسبة لدولة الإمارات العربية المتحدة يكون علي مستوي اتحادي، خاصة وأن تشريعات مكافحة الجرائم البيئية والتغيرات المناخية هي تشريعات اتحادية بالأساس ومأموري الضبط القضائي المتخصصين فيها هم موظفون اتحاديون. The research problem of this study is manifested in standing on the extent of the powers of the Specialized judicial police in climate change crimes and whether they have the same powers established for the general judicial police in the legislation of criminal procedures, or does their power stop at the limit of editing records? And if this is the case, then will the feasibility of this seizure and the goal of its establishment and remarkable expansion be achieved, especially in crimes of a complex technical nature such as climate change crimes? This necessitates studying and analyzing the position of environmental criminal legislation regarding the judicial police necessary to control and track the perpetrators of environmental crimes, especially climate change crimes, and the powers, obligations and duties granted to them in both Egypt and the Emirates, and whether they are sufficient to prosecute such type of newly created crimes. The study concluded with several recommendations, the most important of which are: 1- The need to develop a special and integrated legislative organization for specialized judicial police officers in general and law enforcement officers in the field of environmental crimes and climate change in particular. 2- This legislative regulation should include a clear definition of the powers and powers of judicial police officers specialized in environmental crimes and climate change. 3- That this legislative regulation be general, and for the United Arab Emirates it should be at a federal level, especially since the legislation to combat environmental crimes and climate change are mainly federal legislation and the judicial officers specialized in it are federal employees.
Keywords: التغيرات المناخية -- الجرائم المناخية -- الإجراءات الجزائية -- التنظيمات التشريعية